Caribbean youth development : issues and policy directions (World Bank Washington, D.CUS, 2003)
Examines youth development in the Caribbean. Provides an overview of the risks Caribbean youth are facing, evidence of the protective and risk factors underlying the problems youth are facing, an estimation of costs of risky youth behaviours; and an overview of the policy framework and the types of programmes in place that target youth.
Keywords: YOUTH